Meningkatkan Daya Saing Pemasaran Kue Kering dengan Proses Penataan Produk serta Repacking di Distributor Aydin - Made Iska A. W.; Dewi Retnowati; Setiya Adi Waluyo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Aydin’s distributor is business with the main product is pastries, that distribution with several resselers. Small business that have grown to the present, repacking cookies has not been implemented optimally, not efficient and unable to meet marketing targets significantly.This moment presented are more organized and able to create customer ways among other increase marketing competitiveness by products arrangement that support efficiency, controlling product, so that it can become a magnet in attracting customers. With this hope that performance will be easier and contribute to creating customer desires to come back again. The main operational section is product selling, repacking, delivery and  product collection among many stores. In addition, the selection of research is a business that was started personally and developed with many customers and orders, but there is still a lack of attention to product arrangement. So it is necessary training to improve marketing competitiveness and performance of reseller SMEs management is very important